Pelatihan Administrasi Paud Di Kb Siru Shibyan Desa Cihanjawar Kecamatan Bojong Kab Purwakarta: Indonesia - Ambariah, Aam; Yulianty S, Nadya; Supendi, Dede (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
This writing is the result of Community Service Lecture activities carried out with research studies. This study discusses training in making PAUD administration for teachers at SIRU SHIBYAN KB. The purpose of this study is to understand how this training can bring progress to teachers in making PAUD administration, so that it can be used in everyday learning activities. The method used is descriptive method and data collection techniques namely interviews, observation, and literature study. The results of the study show that training in making PAUD administration can improve skills in making PAUD administration such as the Prota Promes Curriculum, Rppm Rpph. regarding Training on making PAUD administration that was trained in the Training on making PAUD administration above. In turn, these abilities can be transferred to teachers in the Cihanjawar village environment, Bojong sub-district.